REKAYASA ALAT PENYEHATAN UDARA RUANGAN UNTUK MENURUNKAN KADAR GAS KARBONMONOKSIDA (CO) - Chandra Pratama; Imam Khambali; Suprijandani . (GEMA LINGKUNGAN KESEHATAN, 2015)
The concentration of air pollutants inside houses is greater than those outside of houses and most pollutantsconsisted of carbon monoxide (CO)-containing combustion gases that are harmful to health. It is quitenecessaryto innovate air control through engineering procedures such as room air sanitizing devices to lowerthe CO level. The purpose of the study was to determine the effectiveness of a room air-sanitizing device inreducing the levels of COgases.The study was considered as pre-experimental fashioned in a one-group pre-post test design. Theindependent variable was the room air-sanitizing device and the dependent variable was CO concentration.Data was analyzed using paired t-tests.Resultsshowed that there was a reduction in COof 185.3 ppm after passing it throuqh the room air-sanitizingdevice set at a suction flow rate of 2.2 It/min resulting in reduction of 73.9%. Paired t-tests showed a P =0.013 0 (0.05), indicating that there was a significant difference in CO reduction after passing through thedevice. A room sanitizing device is said to be effective when the characteristics and the mass of the activatedcarbon are the same, the contact time of the adsorbate and adsorbent is sufficiently long and the rate of COreduction z 50% of the initial levels.In conclusion, there was a significant reduction in CO after passing through a room air-sanitizing device.However, the reduction could only effectively occur for less than 21 hours. It is recommended to examineother specifications of the actived carbon such as the surface area, density, porosity, and componentcomposition in order to determine factors that contribute. to the differences. Additionally, it is recommendedto engineer device with a simpler design